Susac’s Syndrome: A Case with Unusual Cardiac Vestibular and Imaging Manifestations - Yaron River; Avi Shupak; Beatrice Tiosano; Vika Danilov; Itzhak Braverman (Case Reports in Neurological Medicine)
Susac’s syndrome (SS) is a disease of the microvasculature of the retina, brain, and inner ear. We describe a patient with unusual manifestations of SS with possible involvement of the brainstem, cardiac arrhythmia, and MRI findings lacking the characteristic lesions found in Susac’s syndrome.